Napthrene Compounds from Mycelial Fermentation Products of Marasmius berteroi - Ning Ning Yang; Qing Yun Ma; Fan Dong Kong; Qing Yi Xie; Hao Fu Dai; Li Man Zhou; Zhi Fang Yu; You Xing Zhao (Molecules, 2020)
The metabolites of the genus Marasmius are diverse, showing good research prospects for finding new bioactive molecules. In order to explore the active metabolites of the fungi Marasmius berteroi, the deep chemical investigation on the bioactive compounds from its cultures was undertaken, which led to the isolation of three new naphthalene compounds dipolynaphthalenes A–B (1,2) and naphthone C (3), as well as 12 known compounds (4–15). Compounds 1, 2, and 4 are dimeric naphthalene compounds. Their structures were elucidated by MS, 1D and 2D NMR spectroscopic data, as well as ECD calculations. Compounds 2–4 and 7 exhibited acetylcholinesterase (AChE) inhibitory activities at the concentration of 50 μg/mL with inhibition ratios of 42.74%, 44.63%, 39.50% and 51.49%, respectively. Compounds 5 and 7,8 showed weak inhibitory activities towards two tumor cell lines, with IC50 of 0.10, 0.076 and 0.058 mM (K562) and 0.13, 0.18, and 0.15 mM (SGC-7901), respectively.